Studi Literatur : Pengaruh Faktor Ekonomi Makro Terhadap Kinerja Bisnis Maritim Di Era Pasca-Pandemi COVID-19 - Muhammad Zaki Raihansyah; Azrul Noor; Brian Hadi Wijaya; Akmal Busyra Rizq' Adinata; Denny Oktavina Radianto (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to investigate the influence of macroeconomic factors on the performance of the maritime business in the post-COVID-19 pandemic era. Utilizing a literature review approach, this research analyzes the impact of the COVID-19 pandemic on maritime businesses and its relationship with macroeconomic factors. Prior to the pandemic, the maritime business experienced stable growth, driven by macroeconomic growth and increasing international trade. However, the COVID-19 pandemic has transformed the landscape of the maritime industry by causing a decline in trade volume, increased operational costs, and changes in trade patterns. Macroeconomic factors such as economic growth and market demand dynamics also affect the operational conditions and business strategies of shipping companies. The implications of these findings underscore the need for adaptation and innovation in maritime business practices, including investment in technology and infrastructure, as well as international collaboration to address the challenges faced. Future research can deepen understanding of changes in international trade dynamics and identify more effective adaptation strategies for shipping companies in this post-pandemic era. Thus, this study makes a significant contribution to understanding and addressing the challenges faced by the maritime industry in the future.